Regional Downregulation of Dopamine Receptor D1 in Bilateral Dorsal Lateral Geniculate Nucleus of Monocular Form-Deprived Amblyopia Models - Lin, Dongyue; Wang, Zhonghao; Chen, Wei; Shen, Tao; Qiu, Xuan; Wei, Kun; Li, Jiahui; Yang, Dongsheng; Wang, Ping; Li, Xuri; Yan, Jianhua; Tang, Zhongshu (Frontiers in Neuroscience, 2022)
As a popular eye disease, amblyopia is characterized by the low level of best corrected visual acuity. It starts from early childhood and leads to permanent vision reduction if left untreated. Despite the fact that many young amblyope are well treated in clinical practice, the underlying mechanism remains to be elucidated, which limits not only our understanding of this disease but also therapeutic approach. To investigate the molecular mechanism of amblyopia, primate and rodent monocular deprived amblyopia models were created for mRNA screening and confirmation. We got 818 differentially expressed genes from the dorsal lateral geniculate nucleus (dLGN) of primate amblyopia model. After the Gene Ontology and KEGG enrichments, the main enriched pathways were related to neural development. Interestingly, a particular neurotransmitter pathway, dopaminergic pathway, was identified. The down-regulation of Dopamine Receptor D1 (DRD1) was confirmed in both monkey and mouse samples. Furthermore, immunofluorescence staining indicated that DRD1 was down-regulated in both the ventrolateral region of the contralateral dLGN and the dorsomedial region of the ipsilateral dLGN in the mouse model. The down-regulated regions of DRD1 were exactly the targets of the visual projection from the amblyopic eye. This study suggested that the down-regulation of DRD1 in the LGN may be a cause for amblyopia. And it may also be a reason for the failure of some clinical cases of carbidopa combined levodopa applied to amblyope.